2009
DOI: 10.1177/0265407509106718
|View full text |Cite
|
Sign up to set email alerts
|

Causal beliefs, social participation, and loneliness among older adults: A longitudinal study

Abstract: Loneliness can be seen as a social failure subject to causal search: Why am I lonely? Why do I lack friends? According to attribution theory, answers to these questions can influence emotions, motivation, and behaviours. This study examined the relationships between various affiliative causal beliefs (i.e., beliefs about loneliness and friendship development), social participation, and loneliness among older adults (72+ years). Cross-sectional and longitudinal (over five years) results showed that more strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 38 publications
5
101
0
3
Order By: Relevance
“…Multivariate analysis showed that patients who were severely disabled due to their ophthalmological conditions were less likely to visit hospitals than the other severely disabled patients. Compatible with this finding, it was shown that elderly people with visual impairment and/or blindness have participation restrictions and activity loss that are associated with functional and cognitive decline (6)(7)(8)(9)(10) . In conclusion, blindness gives rise to severe disability and constitutes a large proportion of the diseases that lead to severe disability.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Multivariate analysis showed that patients who were severely disabled due to their ophthalmological conditions were less likely to visit hospitals than the other severely disabled patients. Compatible with this finding, it was shown that elderly people with visual impairment and/or blindness have participation restrictions and activity loss that are associated with functional and cognitive decline (6)(7)(8)(9)(10) . In conclusion, blindness gives rise to severe disability and constitutes a large proportion of the diseases that lead to severe disability.…”
Section: Discussionmentioning
confidence: 87%
“…Visually impaired and blind elderly people usually face restrictions in their ability to participate in various activities. Decreased participation and activity loss are associated with increased risk of functional and cognitive decline; in addition, these patients are at risk of social isolation and may suffer from loneliness (6)(7)(8)(9)(10) . Worldwide, 161-258 million individuals are estimated to be visually impaired, and in 33-39 million of this population, vision is reduced to the level of blindness (11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…Decreased participation and activity loss are associated with an increased risk of functional [57] and cognitive decline in the elderly [58,59]. In addition, those who participate less are at risk with regard to social isolation and may experience feelings of loneliness [60].…”
mentioning
confidence: 99%
“…22,23 Individuals who are aging at home need access to a strong social network, because greater social participation has been shown to be associated with fewer feelings of loneliness. 24 Common opportunities for social integration for older adults are church, libraries, support groups, exercise classes, and senior community centers. Widowed, single, and divorced individuals are at greater risk of social isolation due to feeling disconnected from social groups.…”
Section: Resultsmentioning
confidence: 99%